2013
DOI: 10.1021/pr400591n
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances

Abstract: Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 68 publications
(167 reference statements)
7
45
0
Order By: Relevance
“…These positional variations may be due to protein post-translational modifications (PTMs), different copies of a same gene or protein degradation [26]. Similar positional variations have also been reported in previous studies [27,28]. In addition, some of the specific spots were detected in more than one protein identification (Supplementary Table 3), which were possibly of comigration of multiple proteins [29].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These positional variations may be due to protein post-translational modifications (PTMs), different copies of a same gene or protein degradation [26]. Similar positional variations have also been reported in previous studies [27,28]. In addition, some of the specific spots were detected in more than one protein identification (Supplementary Table 3), which were possibly of comigration of multiple proteins [29].…”
Section: Discussionsupporting
confidence: 79%
“…There were five protein species belonging to the PR-5 group (spots 0014, 1010, 8001, 0012 and 0129) and two protein species belonging to PR-2 group (spots 3206 and 3208) identified. In our study, the allergen Jun a 3 (spots 0014, 8001 and 0012), thaumatinlike protein (spots 1010 and 0129) and glucanase-like protein (spots 3206 and 3208) were identified in multiple spots; post-translational modifications or different isoforms of the same gene product [27] may be present and performing overlapping roles during low temperature stress. However, most of the PR protein species identified were less abundance in T2 and T3 plants than T1 plants (except for spot 0129, which was only detected in T2 gels).…”
Section: Stress Response-related Protein Speciesmentioning
confidence: 50%
“…In fact, proteins related to ATP synthesis, photosynthesis/carbon fixation, glycolysis, and stress and defense were commonly reported as drought and/or salt-responsive proteins from many other organisms 85 . In this study, the levels of proteins related to metabolism were increased in drought- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 20 stressed samples, such as malate dehydrogenase, triosephosphate isomerase, glutamine synthetase, ATP synthase, and triosephosphate isomerase 12,30,52,84,86,87 Table 4 in the Supporting Information). In contrast to the increases in protein abundance, the activities of APX, CAT, SOD, and GST decreased in response to drought stress at the 10 th and 14 th day ( Figure 2).…”
Section: Overall Proteome Responses To Gradual Drought Stressmentioning
confidence: 99%
“…The most commonly increased proteins under drought stress are involved in stress and defense, such as dehydrin, late embryogenesis abundant proteins (LEA), jacalin-related lectin 35, HSPs, 2-cys peroxiredoxin BAS1, and ROS scavenging enzymes, which include GST, APX, Cn/Zn SOD, and GPX12,30,52,84,86,88,89 . In this study, all of these proteins were increased in drought-stressed plants compared to control plants (Supplemental…”
mentioning
confidence: 99%
“…These proteins were associated with functions such as photosynthesis, signal transduction and regulation processes. Valero-Galván et al (2013) showed a decrease in protein abundance/expression mainly those involved in ATP synthesis and photosynthesis upon water withholding/water deficiency in holm oak ( Quercus ilex ).…”
Section: Proteomics Approachmentioning
confidence: 99%